Sustainability assessment of vegetable farms in Northern Tanzania: Multi-stakeholder workshop report - Wilson, Wilson Charles; Mercy Mwambi; Wiston Mwombeki; Ernest, Zablon; Jacob, Theresia; Mvungi, Henry; Solomon, Lisa; Dickson Mushi; Odjo, Sylvanus (CGIAR, 2024)
After conducting fieldwork to assess the sustainability of vegetable agri-food systems in Northern Tanzania between October 2023 and September 2024, we realized the importance of providing feedback on survey results to the stakeholders in the study area and enhancing their awareness and engagement in the FRESH initiative. Therefore, a multi-stakeholder workshop was convened at the New Safari Hotel in Arusha city from 24th to 25th October 2024, followed by a field visit. The participatory workshop was organized to enhance feedback and document the perspective of the farmers and key actors (central and local government actors, private sectors, technicians, and non-governmental organizations) on the sustainability of vegetable production in Arusha and Kilimanjaro regions in Northern Tanzania and propose strategies that could help in improving it. The workshop contributes to the CGIAR’s Strategic Framework, which seeks to support the 2030 agenda for Sustainable Development, in particular, Sustainable Development Goal (SDG) 2 on zero hunger and SDG 13 climate action, through a transformation to more efficient, inclusive, resilient, and sustainable agrifood systems through stakeholder engagement in enhancing national climate actions in fruits and vegetable farming systems in Tanzania for better production and nutrition, a better environment, and decent life, leaving no one behind. The workshop was attended by various partners in the agriculture sector across the Northern highland regions, i.e., smallholder vegetable farmers, vegetable traders, ward extension officers, district and regional agricultural officers, regional trade officers, development partners and research institutes, and the FRESH project team from the CIMMYT and the World Vegetable Centre. Following the introduction and the background of the project and feedback on the accomplished surveys in the study area, the stakeholder was involved in the qualitative assessment of the sustainability of farms, i.e., definition, dimensions, characteristics and challenges, and known strategies for a sustainable farming system (ecological, economic, and social sustainability) during the breakout session facilitated by the FRESH team representatives. In the afternoon session, the project team working on package four (post-harvest …) provided feedback and progress of the project activities i.e. previous pilots on low-cost cooling and the use of packaging solutions. The team introduced the pilot experiment for plastic crate packaging technology in the next session, followed by a breakout group session for further discussion. During the second day, the workshop participants were asked to provide the key takeaways from day one, followed by an overview of the second-day sessions. During the first breakout session, the facilitators led the stakeholders in providing a list of earlier trainings received on sustainable vegetable farming systems in the regions. In the next step, the facilitators led the workshop participants in listing important stakeholders for out scaling the plastic crate packaging technologies and identified the opportunities and constraints for scaling the technology. During the afternoon, the workshop concluded with a field visit to vegetable production demonstration plots in the Meru district.